Adaptive interval type-2 fuzzy controller for nonlinear networked Wiener systems subject to packet dropout and time-varying delay. (September 2022) - El-Nagar, Ahmad M.; Khalifa, Tarek R.; El-Brawany, Mohamed A.; El-Bardini, Mohammad; El-Araby, Essam A.G.
Abstract: In this paper, a novel adaptive interval type-2 fuzzy controller (AIT2FC) is proposed for a class of nonlinear networked Wiener systems under packet dropout and time varying delay. The proposed AIT2FC compensates the negative effects of the packet dropout and time varying delay in both forward and feedback loops. The structure of the proposed AIT2FC has three parts, an adaptive interval type-2 Takagi–Sugeno (IT2TS) fuzzy controller, an IT2TS fuzzy Wiener model (IT2TS-FWM), and a time-varying delay and packet dropout compensator. The adaptive IT2TS fuzzy controller has a cascade connection; an IT2TS fuzzy controller followed by an inverse of an autoregressive moving average (IARMA) system. The nonlinear Wiener system is identified online by an IT2TS-FWM. An adaptive Smith predictor (ASP) is proposed to compensate the negative effects related to the time-varying delay. For each communication channel, the packet dropout is compensated via designing a compensation term in the stochastic Bernoulli approach. Based on the Lyapunov stability (LS) function, the parameters of the proposed AIT2FC are updated online. Also, the learning rates are updated online based on the LS function to avoid singularities and guarantee both the stability and fast convergence of the AIT2FC. The results conclude that the proposed controller is better than the other existing controllers. Highlights: We propose a novel adaptive interval type-2 fuzzy controller based on the Hammerstein approach. The parameters of proposed controller is tuned online based on Lyapunov theorem. The proposed controller is implemented for networked control systems. The proposed controller is implemented practically.